2020
DOI: 10.4093/dmj.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonist Differentially Affects Brain Activation in Response to Visual Food Cues in Lean and Obese Individuals with Type 2 Diabetes Mellitus

Abstract: Background: To investigate the effects of a glucagon-like peptide-1 receptor agonist on functional brain activation in lean and obese individuals with type 2 diabetes mellitus (T2DM) in response to visual food cues. Methods: In a randomized, single-blinded, crossover study, 15 lean and 14 obese individuals with T2DM were administered lixisenatide or normal saline subcutaneously with a 1-week washout period. We evaluated brain activation in response to pictures of high-calorie food, low-calorie food, and nonfoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Hypertriglyceridemia is a common symptom of diabetes which was also found in T2DM patients in our study; the correlation results indicate the important roles of the fusiform and lingual gyrus in the neural pathways of lipid metabolism. In addition, a positive correlation was found between the 2 h postprandial insulin and the decreased inflow from the left fusiform gyrus to the left lingual gyrus, which is interpretable as previous research reported that the plasma insulin level is associated with cue-induced appetite at both neural and behavioral levels, which can affect activation of the fusiform gyrus in response to visual processing [ 30 , 31 ]. Furthermore, 2hPG was positively correlated with the increased inflow from the left fusiform gyrus to the right MFG.…”
Section: Discussionsupporting
confidence: 70%
“…Hypertriglyceridemia is a common symptom of diabetes which was also found in T2DM patients in our study; the correlation results indicate the important roles of the fusiform and lingual gyrus in the neural pathways of lipid metabolism. In addition, a positive correlation was found between the 2 h postprandial insulin and the decreased inflow from the left fusiform gyrus to the left lingual gyrus, which is interpretable as previous research reported that the plasma insulin level is associated with cue-induced appetite at both neural and behavioral levels, which can affect activation of the fusiform gyrus in response to visual processing [ 30 , 31 ]. Furthermore, 2hPG was positively correlated with the increased inflow from the left fusiform gyrus to the right MFG.…”
Section: Discussionsupporting
confidence: 70%
“…The number of participants per study ranged from 8 to 48. Five studies recruited an equal ratio of males and females, whereas six studies recruited females only, and four studies recruited males only (Table 1 ) [ 16 - 39 ]. Twelve studies recruited healthy subjects only, and numerous studies recruiting subjects with overweight/obesity and type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a negative association, weaker compared to reward areas but still significant, was observed both for oxyntomodulin and glicentin with the activation of the hypothalamus. Greater activation of the hypothalamus has recently been reported in people with obesity compared to lean individuals with T2DM 15 . Additionally, hypothalamic activation was reduced after treatment with the GLP‐1RA lixisenatide among individuals with obesity who had decreased their caloric intake 15 .…”
Section: Discussionmentioning
confidence: 96%
“…Greater activation of the hypothalamus has recently been reported in people with obesity compared to lean individuals with T2DM. 15 Additionally, hypothalamic activation was reduced after treatment with the GLP-1RA lixisenatide among individuals with obesity who had decreased their caloric intake. 15 However, given that the hypothalamus hosts both orexigenic and anorexigenic pathways, it is difficult to assess the net impact on appetite and energy intake of the negative association of hormonal levels with hypothalamic activation that we observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation